2020
DOI: 10.3168/jds.2020-18158
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the viability of Staphylococcus aureus and production of enterotoxin during processing and storage of white-brined cheese

Abstract: Staphylococcus aureus is a major foodborne pathogen that causes severe disease in humans. It is commonly found in milk and dairy products, particularly in fresh brined cheese. Our aim was to investigate the behavior of Staph. aureus and enterotoxin production during the storage of white-brined cheese prepared with or without a starter culture and stored in a 10 or 15% NaCl brine at 10°C and 25°C for 28 d. NaCl concentration, water activity, pH, and number of Staph. aureus and lactic acid bacteria were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…This contamination is most common among unpasteurized dairy products, which is especially true of products manufactured largely by hand [ 31 ]. Moreover, it has been observed that the number of staphylococci increases during the storage of products [ 32 ] which was also observed in our research. This is due to the ability of S. aureus to grow rapidly in milk and dairy products, and also due to the contamination of cheese makers’ skin.…”
Section: Resultssupporting
confidence: 88%
“…This contamination is most common among unpasteurized dairy products, which is especially true of products manufactured largely by hand [ 31 ]. Moreover, it has been observed that the number of staphylococci increases during the storage of products [ 32 ] which was also observed in our research. This is due to the ability of S. aureus to grow rapidly in milk and dairy products, and also due to the contamination of cheese makers’ skin.…”
Section: Resultssupporting
confidence: 88%
“…These results were consistent with those from previous studies in Saint-Nectaire-model cheese made from cows’ raw milk [ 15 ], similar to our cheese models, in which no staphylococcal enterotoxin was detected, although coagulase-positive staphylococci counts were around 5 Log CFU/g at D0.25, a propitious condition to SE accumulation. The increase in the S. aureus counts with the 10-fold reduced lactic starter dose are similar to those reported by Al-Nabulsi et al [ 53 ] in white brined cheeses manufactured without a lactic starter. Using standard brine (10% of NaCl) and a storage temperature of 25 °C, the authors showed reductions by 1.17 Log [CFU/g] and by 0.56 Log [CFU/g] at D1 and at D28, respectively, between the cheeses manufactured without and with a lactic starter.…”
Section: Discussionsupporting
confidence: 89%
“…The family Enterobacteriaceae includes some severe foodborne pathogens, including toxin producing Shigella spp., Salmonella spp., and some serotypes of E. coli , such as E. coli O157:H7 [ 64 ]. Among the Staphylococcus spp., S. aureus , which is commonly detected in cheeses, is an important foodborne pathogen and disease-causing bacterium in humans [ 65 ]. Moreover, two cheeses had low relative abundance of the species C. perfringens .…”
Section: Discussionmentioning
confidence: 99%